Merging species?: Evidence for hybridization between the eel parasites Anguillicola crassus and A. novaezelandiae (Nematoda, Anguillicolidea) - Grabner, Daniel S.; Dangel, Kerstin C.; Sures, Bernd (Parasites & Vectors, 2012)
Background: The eel parasitic nematodes Anguillicola crassus (originating from Asia) and Anguillicola novaezelandiae (originating from New Zealand) were both introduced to Europe, but occurred in sympatry only in Lake Bracciano in Italy, where they both infected the European eel (Anguilla anguilla). A. novaezelandiae was introduced to the lake in 1975 and disappeared soon after A. crassus was also found there in 1993. We tested the hypothesis if hybridization of the two species might be an explanation for the findings at Lake Bracciano. Findings: After laboratory infection of one European eel with 10 third stage larvae of each parasite, two living female and 4 male adults of each species were found to co-occur in the swim bladder after 222 days post exposure. In 9 out of 17 eggs, isolated in total from uteri of the two A. novaezelandiae females, alleles were detected by microsatellite analysis that are characteristic for A. crassus, suggesting the hybrid origin of these eggs. In contrast, none of the eggs isolated from A. crassus females possessed alleles different from those found in A. crassus adults, but it was revealed that one female can be inseminated by several males. Conclusion: Our results show that A. crassus and A. novaezelandiae can co-infect a single eel and can mature together in the same swim bladder. We also provide evidence for the possibility of hybridization of A. crassus males with A. novaezelandiae females. Therefore, hybridization might be an explanation for the disappearance of A. novaezelandiae from Lake Bracciano.